Optimasi Pemograman Sistem Pengendalian Mesin CNC Pengebor PCB Berdasar Metode Firefly Algorithm - Hidayatul Nurohmah; Machrus Ali; Rukslin; Dwi Ajiatmo; M. Teguh Proyoga (Program Studi Teknik Elektro S1 ITN Malang, 2022)
Automatic circuits use several electronic components found on Printed Circuit boards ( PCB ), namely micro (small) sized boards. With more holes in the PCB, it is more time-consuming to drill them manually with human power. In addition, accuracy is required when the drill bit contacts the PCB board, which may cause drilling errors due to friction. This project aims to create an autonomous drill using a computer and BCNC software to move it live. DC stepper and spindle motors powered by a PID firefly-controlled motor drive this machine. Drilling is carried out using the BCNC program, the drilling process is carried out by entering codes in the form of codes that can later be read by the CNC. By changing the layout to what is known as a code, the coordinates of the holes that have been made in the layout can be found. PCB designing software is used for this procedure. With each of the ten experiments used to test the accuracy of the six axes, an error value of 1.2% was recorded. Kp = 54, Ki = 38, and Kd = 0.9 are constant values obtained from the PID implementation on DC stepper.